MOLECULAR DETECTION OF GENES ENCODING CLUMPING FACTOR (CTFA), THERMONUCLEASE (NUC) AND IMMUNOGLOBULIN G BINDING REGION OF PROTEIN A (SPA)FROM METHICILLIN RESISTANCE STAPHYLOCOCCUS AUREUS ISOLATED FROM BOVINE MASTITIS. - Basim Mohammed Hanon (Basrah Journal of Veterinary Research)
The Staphylococcus aureus responsible for intramammary infection in bovine andis the main etiological agent of clinical and subclinical mastitis in dairy herds. In thisstudy a total of 64 Staphylococcus aureus strain obtained from 112 samples from mastitiscow (57.14%). S. aureus strain were identified phenotypically and further characterizedgenotypically by polymerase chain reaction PCR. Amplification of genes encodingspecific species for S. aureus(Sau), clumping factor (ctfA), thermonuclease (Nuc) and thegene segment encoding the immunoglobulin G binding region of protein A gene spa. Theamplification of Sau gene produce amplicon in a molecular size proximally 530bp in allstrain, the produce amplicon in a molecular size proximally size 980 bp in ctfA gene(73.43%) andImmunoglobulin G binding region of spa gene produce amplicon in a sizeproximally 950 bp was observed in 43 and 3 strain amplicon in a size proximally 390 bp(71.87%). The thermonuclease gene the amplicon in a size proximally 279 bp with(90.62%). After that methicillin resistance (MRSA) were detected in a percentage(21.87%), all of these strain of MRSA contain all virulence genes.